Adult picky eaters with symptoms of avoidant/restrictive food intake disorder: comparable distress and comorbidity but different eating behaviors compared to those with disordered eating symptoms. Issue 1 (December 2016) - Zickgraf, Hana; Franklin, Martin; Rozin, Paul
Abstract Background One presentation of Avoidant/Restrictive Food Intake Disorder (ARFID) is characterized by picky eating, i.e., selective eating based on the sensory properties of food. The present study has two aims. The first is to describe distress and impairment in individuals with ARFID secondary to picky eating. The second is to determine whether eating behaviors hypothesized to be specific to picky eating can differentiate picky eaters with and without ARFID from typical eaters (e.g., individuals not reporting picky or disordered eating) and individuals who strongly endorse attitudes associated with anorexia and bulimia (eating disordered attitudes). Methods Participants were recruited from Amazon's Mechanical Turk (N = 325) and an online support group for adult picky eaters (N = 81). Participants were grouped based on endorsement of picky eating, ARFID symptoms, and elevated eating disordered attitudes on the Eating Attitudes Test (EAT-26). The resulting four eating behavior groups were compared on measures of distress and impairment (e.g., anxiety/depression and, obsessive compulsive disorder symptoms, eating-related quality of life) and on measures of eating behaviors associated with picky eating (e.g., food neophobia, inflexibility about preparation and presentation of preferred foods, sensitivity to sensory stimuli, and eating from a very narrow range of foods). The groups were compared using one way ANOVA with post-hoc Tamhane's T2 tests. Results On measures of distress and impairment, participants with ARFID reported higher scores than both typical eaters and picky eaters without ARFID, and comparable scores to those with disordered eating attitudes. Three of four measures of picky eating behavior, eating inflexibility, food neophobia, and eating from a range of 20 or fewer foods, distinguished picky eaters with and without ARFID form typical eaters and those with disordered eating attitudes. Picky eaters with ARFID reported greater food neophobia and eating inflexibility, and were more likely to eat from a narrow range of foods, compared to picky eaters without ARFID. Conclusions Adult picky eaters can be differentiated from those with symptoms of anorexia and bulimia by their stronger endorsement of food neophobia and inflexible eating behaviors, and by eating from a very narrow range of foods. Picky eaters with ARFID symptoms can be differentiated from picky eaters without these symptoms on the basis of these three eating behaviors, and by their higher endorsement of internalizing distress, OCD symptoms, and eating-related quality of life impairment. This study provides evidence that ARFID symptoms exist independently of symptoms of other eating disorders and are characterized by several distinct eating behaviors. In a clinical analogue sample of disordered eaters, ARFID symptoms were associated with distress and impairment at levels comparable to symptoms of anorexia and bulimia.